Analysis Of Macro Nutritional Content Of Chicken Nuggets Substitution Of Young Jackpots And Soy Flour As An Alternative To A High Fiber Snack For Obese Teenagers - Tita Purwaningsih; Lilia Faridatul Fauziah (Jurnal EduHealth, 2024)
Obesity is a disorder characterized by excessive accumulation of fat tissue in the body. Therefore, additional food with high daily fiber intake is needed. One of them is by providing additional food in the form of young jackfruit and soy flour substitute nuggets. This study aims to determine the macronutrient content and acceptability of nuggets as an alternative high-fiber snack. This study used the True Experimental Design method with a Completely Randomized Design (CRD) with 4 levels of young jackfruit and soy flour substitution treatment, namely F0 (100:0:0), F1 (45:45:10), F2 (35:50:15) and F3 (15:65:20). Preliminary research, namely organoleptic quality tests of 30 panelists and ranking tests to show the best formulation, continued with proximate analysis and nugget fiber content. The results of the study showed that there was an effect of increasing fiber content in nuggets, with the highest fiber content in the F3 treatment. Significant effect on the color and texture of young jackfruit substitution and Kruskal Wallis soybean flour (P Value <0.05). The best treatment was in F2. The conclusion of this study is that young jackfruit and soybean flour substitution nuggets show an effect on the levels of calories, protein, fat, carbohydrates, ash, water, fiber, and acceptability in the color and texture categories of nuggets. Obese adolescents are advised to consume 100 grams of fried F2 nuggets per day to meet 95.58% of fiber needs.